Compensation schemes for learning a Lingua Franca in the European Union. (2nd April 2018) - Ginsburgh, Victor; Moreno‐Ternero, Juan D.
Abstract: We discuss compensation schemes that should give incentives to EU countries and citizens to acquire a lingua franca . We consider three possible candidate languages: English, French and German, which are already the most widely spoken languages. In our model, countries can claim compensations linked to the number of (young) citizens who do not speak a given candidate language, and the distance between the official language in the country and the suggested lingua franca . We study two sharing schemes that are rooted in ancient sources: the Aristotelian proportional rule and the Talmud rule. The former prevents coalitional manipulations among countries, whereas the latter guarantees meaningful lower bounds in the sharing process for all countries.